Cognitive dysfunction and amyloid β accumulation are ameliorated by the ingestion of green soybean extract in aged mice. (April 2015) - Unno, Keiko; Konishi, Tomokazu; Nakagawa, Aimi; Narita, Yoshie; Takabayashi, Fumiyo; Okamura, Hitomi; Hara, Ayane; Yamamoto, Hiroyuki; Iguchi, Kazuaki; Hoshino, Minoru; Yasui, Kensuke; Katayanagi, Yuki; et al.
Highlights: The intake of green soybean extract ameliorates cognitive dysfunction of aged mice. The high expression of Ptgds was significantly associated with green soybean diet. The high expression of Ptgds suggested an increase of amyloidβ (Αβ)-chaperone. The expression of Aplp1, an amyloid precursor protein, was significantly reduced. The amount of Αβ 40 and 42 was reduced in the brain of aged mice fed green soybean. Graphical Abstract: Abstract: The effects of soybean extracts were investigated in senescence-accelerated (SAMP10) mice, a mouse model of brain senescence with cognitive dysfunction. Mature soybeans are usually yellow. However, the green soybean retains green color after being ripened. Cognitive functions were significantly better-preserved in aged mice fed green soybean than age-matched control mice with or without yellow soybean feeding. Molecular mechanisms of the beneficial effect of green soybean on brain functions were examined through transcriptome analysis of SAMP10 hippocampus. The high expression of Ptgds was significantly associated with green soybean diet, which encodes lipocalin-type prostaglandin D2 synthase, a putative endogenous amyloid β(Αβ)-chaperone. In consonance, Aplp1 expression was significantly reduced, a member of amyloid precursor proteins. Furthermore, the amount of Aβ 40 and 42 was reduced in the insoluble fraction of cerebral cortex. These results suggest that the intake of green soybean ameliorates cognitive dysfunction of aged mice through the reduction of Aβ accumulation.